Pengaruh Reformasi Penggajian Terhadap Motivasi dan Kinerja Karyawan - Adinda Thalia Salsabila; Muhammad Habibi; M. Hanif Ash Shiddiqi; Muhammad Iqbal; Rindu Oktavia; Septa Adri Fania; Syamsir Syamsir (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Salary reform as a structural improvement in a company’s compensation system is a widely applied strategy to enhance employee motivation and performance. Compensation policies that are responsive to employee needs are expected to create a work environment that supports productivity, where intrinsic motivation can be strengthened through fair and proportional rewards. This study aims to explore the extent of the influence of salary reform on improving employee motivation and performance within organizations by using a literature review method. Based on analyses of previous studies, it was found that salary reform not only plays a significant role in fostering employees' intrinsic motivation but also impacts the overall productivity of the organization. Reforms that include salary structure adjustments, performance-based incentives, and increased transparency in compensation management have proven effective in reducing disparities, enhancing loyalty, and improving workplace climate. These findings strongly imply that management should continuously develop adaptive compensation policies focused on employee needs and well-being, with the aim of optimally contributing to achieving the company’s strategic goals and enhancing organizational competitiveness.